2023
DOI: 10.1001/jamanetworkopen.2022.55770
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tele-Emergency Consultations on Pediatric Interfacility Transfers

Abstract: ImportancePediatric referral centers are increasingly using telemedicine to provide consultations to help care for acutely ill children presenting to rural and community emergency departments (EDs). These pediatric telemedicine consultations may help improve physician decision-making and may reduce the frequency of overtriage and interfacility transfers.ObjectiveTo examine the use of pediatric critical care telemedicine vs telephone consultations associated with risk-adjusted transfer rates of acutely ill chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
(86 reference statements)
2
8
0
Order By: Relevance
“…21,22 Although unmeasured confounders and protocol deviations could have contributed to biased results, the previously published baseline characteristics comparing patients who received consultations that adhered to the study group and those whose consultations deviated from the study group intervention were similar. 11 We also did not identify any significant differences by intention-to-treat, per-protocol, or treatment-received analyses. In addition, despite use of a previously validated medication error instrument, medication errors and their outcomes are somewhat subjective in nature, and the interrater reliability between pharmacists was only moderate, potentially impacting the validity of the findings.…”
Section: Jama Network Open | Emergency Medicinementioning
confidence: 86%
See 4 more Smart Citations
“…21,22 Although unmeasured confounders and protocol deviations could have contributed to biased results, the previously published baseline characteristics comparing patients who received consultations that adhered to the study group and those whose consultations deviated from the study group intervention were similar. 11 We also did not identify any significant differences by intention-to-treat, per-protocol, or treatment-received analyses. In addition, despite use of a previously validated medication error instrument, medication errors and their outcomes are somewhat subjective in nature, and the interrater reliability between pharmacists was only moderate, potentially impacting the validity of the findings.…”
Section: Jama Network Open | Emergency Medicinementioning
confidence: 86%
“…This may be due to the inaccuracies, rounding errors by the CPOE, or even the discrepancies in acceptable dose by different pharmacologic references. 7,16 Although research suggests that telemedicine consultations can improve communication and quality of care and reduce unnecessary transfers, 11,17 the evidence supporting telemedicine to reduce medication errors is limited. One previous study 9 by our group found that using telemedicine consultations in the ED was associated with decreased physician-related medication errors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations